Diagnostic Accuracy of Serum Bilirubin and Magnetic Resonance Cholangiopancreatography for Differentiating Benign from Malignant Extrahepatic Obstructive Jaundice: A Histopathology-Referenced Study - Muhammad Faisal; Muhammad Hafidh Komar; Theodorus (Sriwijaya Journal of Surgery, 2026)
Background: Differentiating benign from malignant extrahepatic obstructive jaundice before surgery determines whether patients are triaged towards curative or palliative treatment. Objective: To evaluate the diagnostic accuracy of serum bilirubin and magnetic resonance cholangiopancreatography (MRCP) against histopathology. Methods: This STARD-compliant, single-centre retrospective diagnostic-accuracy study included 50 consecutive adults treated at Dr. Mohammad Hoesin Central General Hospital, Palembang between January 2024 and December 2025. Serum bilirubin and MRCP were assessed against surgical or biopsy histopathology. Receiver-operating-characteristic analysis and 2×2 tables with Wilson 95% confidence intervals were computed. Results: Thirty-nine patients (78%) had benign and 11 (22%) malignant aetiology. Direct bilirubin (13.7 vs 8.7 mg/dL; p=0.003), total bilirubin (20.17 vs 13.02 mg/dL; p=0.007), and common bile duct dilation (26.0 vs 18.5 mm; p=0.018) were higher in malignancy. Direct bilirubin had an AUC of 0.797 at 9.65 mg/dL; total bilirubin had an AUC of 0.773 at 14.3 mg/dL. MRCP had 94.9% specificity, 63.6% sensitivity, and 88.0% accuracy. Conclusion: Serum bilirubin is a sensitive early rule-out marker, whereas MRCP is a highly specific confirmatory tool; their sequential use may improve pre-operative triage.